Hedging Effectiveness as an International Financial Risk Management Strategy - Zakaria, Syawal (Golden Ratio of Mapping Idea and Literature Format, 2023)
In the dynamic landscape of global finance, businesses face intricate challenges navigating international markets, necessitating robust risk management strategies. This explores the evolution of hedging as a crucial financial maneuver originating from the 20th-century financial upheavals. Hedging, strategically responding to market fluctuations, has transformed into a sophisticated risk management tool, requiring a nuanced understanding of market dynamics. It serves as a financial shield, particularly in the face of currency fluctuations and interest rate volatility for multinational corporations. The symbiotic relationship between theoretical underpinnings and practical application becomes evident as the narrative unfolds. The story emphasizes the complexities and challenges of financial markets, highlighting the need for strategic and proactive responses. The effectiveness of hedging is portrayed not as a one-size-fits-all solution but as a philosophy ingrained in decision-making processes for businesses operating globally. Real-world case studies dissect the successes and failures of companies employing hedging, bridging theory and application. Hedging is portrayed not as a static set of practices but as a dynamic philosophy adapting to technological advancements. The integration of sophisticated algorithms and artificial intelligence transforms risk management, enabling more precise, agile, and adaptive hedging approaches.